Poisoning – An Important Cause of Emergency Admission and Death Toll - Sarker, Prof. Dr. HN (The Planet, 2021)
Poisoning is a significant global public health problem.1 It is also an important health problem in Bangladesh. It is one of the important causes of patient admission to emergency department and Intensive Care Units (ICU). It is estimated that around 3,00,000 poisoning per year occur in Bangladesh and cost around 2000 death per year.2 There is no poison information center in Bangladesh, so accurate incidence is difficult to know.3 The adverse consequences of poisoning are higher in underdeveloped and developing countries because of presence of weak health regulations and poor health care services.4 Poisoning is common in our society having significant morbidity and mortality. Poisoning may be suicidal, homicidal and accidental. Parasuicide is a term used to mean the show or pretend to poison himself/herself to draw sympathy and not to die. Poisonous snake bite and poisonous fish like puffer fish poisoning are also a significant cause of poisoning. Female patients and young people of second and third decades accounted for the majority of the cases.5,6,7 Suicidal poisoning accounted for 78% of cases.8,9 Organophosphate insecticides and herbicides are the most commonly ingested poisons and second common is sedetives.10 Government regulations, educational awareness and poison information center will help to decrease the growth of this public health problem. Public health measures to improve prevention of selfharm could potentially reduce morbidity and mortality related to poisoning, with opportunities to increase mental health support to reduce suicidal ingestions. Limiting the use of insecticides and herbicides, and replacing them with the newer least toxic agents may also be useful in this aspect.